Relative abundance and population biology of the non-indigenous crab Charybdis hellerii (Crustacea: Brachyura: Portunidae) in a southwestern Atlantic estuary-bay complex - Sant'Anna, Bruno Sampaio; Watanabe, Timoteo Tadashi [UNESP]; Turra, Alexander; Zara, Fernando Jose [UNESP] (Regional Euro-asian Biological Invasions Centre-reabic, 2012)
Invasive species are potential threats to biodiversity, especially if they become established and outnumber native species. In this study, a population of the non-indigenous crab Charybdis hellerii was analyzed in an estuary-bay complex on the southeastern Brazilian coast, with respect to its abundance relative to sympatric native brachyuran species, as well as the size structure, sexual maturity, sex ratio, frequency of mutilation, reproductive period, and development of the reproductive system. Crabs were sampled monthly both in the intertidal zone of rocky shores and on sublittoral soft-bottom. Nine species were recorded on the rocky shores, where C. hellerii was the second most abundant species; only three individuals of C. hellerii were collected in the sublittoral samples. This population of C. hellerii showed a unimodal size structure composed mainly of mature individuals; males were larger than females, and the sex ratio was skewed toward males (3.1:1). About 46.9% of the individuals (75 of 160 crabs) had mutilated or regenerating appendages, more frequent in males (56.8%) than in females (28.2%), which may reflect both inter- and intraspecific agonistic interactions. A continuous reproductive pattern is suggested for this population, although ovigerous females occurred unevenly during the year, with 58.82% of them being collected in winter. There was evidence of multiple spawning, since the ovigerous females with an initial egg mass showed mature ovaries as well as seminal receptacles filled with sperm. C. hellerii is well established in the estuary-bay complex, but is concentrated in intertidal and shallow subtidal rocky shores, where it may compete with and replace other species such as the portunid Cronius ruber. This study also highlights the importance of systematic monitoring studies to evaluate the effects of the introduction of non-indigenous species on ecologically similar natives.
Keywords: Brachyura; Portunidae; invader crab; Estuary